RPC BINJAI 105.4 FM RADIO BROADCASTING MANAGEMENT STRATEGY IN FACING THE DIGITAL ERA - Winda Kustiawan; Muhammad Rishan Sahlaya; Muhammad Dimas Nugroho; Muhammad Aziz Syahridani; Annisa Fatika; Reti Miranda Deansyah; Wahyuni Pulungan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The development of digital technology requires radio media to make strategic adaptations to maintain its existence amidst changes in public media consumption patterns. This study aims to analyze the broadcast management strategy of Radio RPC Binjai 105.4 FM in facing the digital era using a descriptive qualitative approach. Research data were obtained through in-depth interviews, observations, and documentation of broadcast activities and radio digital media management. The results show that Radio RPC Binjai 105.4 FM implements adaptive strategies through the use of social media as a means of promotion and interaction with listeners, strengthening the role of broadcasters as influencers, adjusting broadcast content to audience characteristics, especially the younger generation, utilizing digital technology in the broadcasting process, and managing revenue sources that rely on advertising and media collaboration. These findings confirm that the sustainability of local radio in the digital era can be achieved through broadcast management that is integrated, contextual, and responsive to the dynamics of digital media.